Pengenalan Teknologi Sensor Cahaya Untuk Meningkatkan Minat Belajar Siswa Sekolah Dasar - Sirojul Hadi; Siti Soraya; Puspita Dewi; Khairan Marzuki; Lalu Ganda Rady Putra; Regina Pricilia Yunika (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2020)
Education is an effort to build a better human civilization and eliminate human suffering caused by ignorance and underdevelopment in science and technology. In this research, a workshop was held to introduce light sensor technology to enhance elementary students' interest in learning about technology. This research was conducted at SDN 3 Mataram. The research was carried out by dividing 40 participants into 5 groups with each group guided by one mentor. Each group will be guided by a mentor to practice making light sensor technology until the light sensor circuit to turn on the lights can function properly. To find out students' interest in learning is done by making a questionnaire before and after doing the practice. The results obtained from the questionnaire that there is no significant difference between the understanding at the pre test and post test